PENGARUH MATERIALISME, SPIRITUALITAS DAN PERILAKU BERHEMAT TERHADAP KELEBIHAN BERHUTANG. STUDI PADA APARATUR SIPIL NEGARA DI KOTA KUPANG. - Janri D. Manafe (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to investigate the direct effect of materialism, spirituality and frugality behavior on excess debt. Data were obtained from 164 ASN in Kupang City who were willing to act as respondents. This research questionnaire consists of measuring instruments of constructs that influence and are influenced in the research model plus demographic data from the respondents. The data obtained were then analyzed with a quantitative approach using multiple regression analysis tools. The results of this study indicate that materialism, spirituality and frugal behavior are factors that can form excess debt among ASN in Kupang City. It is hoped that with the results of this research, practitioners and academics can gain additional knowledge in order to enrich the literature on the advantages of debt in Indonesia, which until now is still considered necessary to be added.